Solvent Extraction of Indium(III) with Alizarin into 1-Octanol - Jadhav, S.D.; Turel, Z.R. (Asian Journal of Chemistry, 2010)
The teagent alizarin has been used for the extraction of indium(III) into 1-octanol. The effect of various parameters on the extraction coefficient value of indium(III) has been evaluated. The stoichiometry of metal to reagent, determined by the method of substoichiometric extraction and slope ratio was found to be in the ratio of 1 : 3. Separation factor for a number of elements in the extraction of indium(III) has been evaluated.